Design of the double-layer spray greenhouse spray system and its cooling effects - Xu, Jihang; Sun, Weizhen; Wang, Jian; Shu, Sheng; Tan, Thanming (International Journal of Agricultural and Biological Engineering, 2025)
The existing plastic greenhouses in the Yangtze River Basin experience high temperatures in summer and low temperatures in winter, significantly impacting year-round greenhouse production. Double-layer plastic film greenhouses possess excellent thermal insulation in winter but suffer from high temperatures in summer. Spray cooling is an effective method for reducing summer temperatures in greenhouses, yet direct spraying increases the indoor humidity, which is detrimental to crop growth. To address these problems, the research team designed a double-layer spray greenhouse in which a spray system composed of nozzles was placed between the two layers of plastic films. This paper simulated the indoor temperature field of a greenhouse under different nozzle layouts using Computational Fluid Dynamics (CFD) software to identify the optimal spray system. Based on this analysis, the practical effectiveness of a double-layer spray greenhouse was examined, thereby providing theoretical justification for its promotion and application. The key findings are as follows: 1) When the nozzle spacing was 0.8 m, the nozzle was placed 0.2 m from the inner arch top, and the nozzle sprayed downwards, the average temperature inside the greenhouse was the lowest, representing the optimal nozzle layout. 2) Compared to a single-layer multispan greenhouse, the double-layer spray greenhouse had a higher average indoor temperature of 1.18°C in spring, with a lower average indoor temperature of 2.14°C in summer. The growth, yield, and fruit quality (soluble solids content, vitamin C content, and soluble sugar content) of tomatoes in the double-layer spray greenhouse were superior to those in the single-layer multispan greenhouse.Keywords: greenhouse, spray system, CFD, nozzle layoutDOI: 10.25165/j.ijabe.20251805.9483Citation: Xu J H, Sun W Z, Wang J, Shu S, Tan Z M. Design of the double-layer spray greenhouse spray system and its cooling effects. Int J Agric & Biol Eng, 2025; 18(5): 76–89.